Copper-catalyzed 4-HO-TEMPOH mediated phosphorylation of alkenes - Zhan, Jun-Long; Wang, Bing-Jie; Wang, Chen-Xi; Zhao, Xin-Ming; Zhou, Sai-Nan; Dou, Zao-Zao; Yang, Xin-Xin; Zhu, Lin; Ren, Wei (Organic & biomolecular chemistry, 2023)
An efficient, practical and regioselective synthesis of ( E )-alkenylphosphine oxides has been developed starting from alkenes under copper catalysis and 4-HO-TEMPOH oxidation. Preliminary mechanistic studies clearly reveal that a phosphinoyl radical is involved in this process. Moreover, this method features mild reaction conditions, good functional group tolerance, and excellent regioselectivity and also promises to be efficient for the late-stage functionalization of drug molecular skeletons. The reaction will create an opportunity for the synthesis of complex phosphorus containing bioactive molecules. A copper-catalyzed unprotected hydroxylamine mediated phosphorylation of alkenes furnished structurally important ( E )-alkenylphosphine oxides under mild reaction conditions with good functional group tolerance and excellent regioselectivity.